Implementação de um pré-regulador de fator de potência utilizando um conversor CC-CC boost - Lemos, Leandro Coradi Teixeira de (2014)
The conventional rectifiers have input current with high harmonic distortion and low power factor, wasting power to the supply of dc loads. One of the existing solutions is the use of dc-dc converters for active power factor correction. This research presents a technique of correction of the power factor called PFC boost, which consists of the input bridge rectifier, the power stage and the boost control where the integrated circuit UC3854 was used. Its characteristic are: sinusoidal input current in phase with the input voltage, as well as regulation of the output voltage. Simulations and experimental results has demonstrated the power factor correction.